TERA- A Tool for Aero-engine Modelling and Management - Ogaji, Stephen O. T.; Pilidis, Pericles; Hales, Richard (Cranfield University, 2007)
One of the distinguishing features of the civil aero-engine market is its high competitiveness. The costs and risks associated with new projects are such that the difference between two apparently equally attractive options could result in success from one and a threat to the survival of the company from the other. To conceive and assess engines with minimum global warming impact and lowest cost of ownership in a variety of emission legislation scenarios, emissions taxation policies, fiscal and Air Traffic Management environments, a Techno-economic and Environmental Risk Assessment (TERA) model is needed. TERA incorporates multi-disciplinary modules for modelling gas turbine and aircraft performance, estimation of engine weight, noise and emissions as well as environment impact and operating economics. The TERA software is integrated with a commercial optimiser and provides a means for cycle studies. It is to be expected that new legislative and fiscal constraints on air travel will demand an extension to the customary range of asset management parameters. In such a business environment there is potential for TERA to develop into a useful tool for aircraft and engine asset management. This paper presents a description of this tool as well as gives some results from scenario studies.
Keywords: Gas Turbine; Environment; Global Warming Potential; Emissions; Noise; Optimisation; Risk Assessment; Techno-economic